Implementation and Evaluation of Teachers’ Performance Supervision at Madrasah Aliyah (Islamic Senior High School): A Case Study of MAN 2 Banjarmasin and MAN 3 Banjarmasin - Tambrin, Muhammad; Wasliman, Iim; Hanafiah, Hanafiah; Mudrikah, Achmad (Journal of Education Research and Evaluation, 2021)
Scrutinizing the education quality should include teachers as a forefront in the education world. Even a good curriculum and programs will be meaningless if teachers do not implement them responsibly and consistently. This study aims to determine; (1). How is the teachers’ performance supervision program in MAN 2 Banjarmasin and MAN 3 Banjarmasin; (2) How is the organizing program for teachers’ performance supervision in MAN 2 Banjarmasin and MAN 3 Banjarmasin; (3). How are the movement and leadership of teachers’ performance supervision in MAN 2 Banjarmasin and MAN 3 Banjarmasin; (4) How to control teacher performance supervision effectiveness in MAN 2 Banjarmasin and MAN 3 Banjarmasin. (5) How are the creative and innovative ideas in actualizing teachers’ performance supervision effectiveness in MAN 2 Banjarmasin and MAN 3 Banjarmasin. Meanwhile, the results of this study were; (1) the planning program had not been implemented effectively due to problems of limited resources; (2) organizing supervision had not been carried out optimally; (3) the movement and leadership had run relatively well; however, improvements are still required in the managerial aspects of leadership; (4) controlling the effectiveness of teachers’ performance supervision was gradually conducted; (5) creative and innovative ideas emphasized the strengthening of teachers’ performance supervision Madrasah Aliyah education units and e-Kinerja application. In addition, implementation and evaluation of teachers’ performance supervision in MAN 2 Banjarmasin and MAN 3 Banjarmasin had been implemented in accordance with the Standard Operating Procedures (SOP) issued by the Ministry of Religion of the Republic of Indonesia. Nevertheless, the results were still ineffective due to problems of various resource limitations.